1994
DOI: 10.1161/01.cir.89.2.694
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transcutaneous electrical nerve stimulation on coronary blood flow.

Abstract: Transcutaneous electrical nerve stimulation can increase resting coronary blood flow velocity. The findings suggest that the site of action is at the microcirculatory level and that the effects may be mediated by neural mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(56 citation statements)
references
References 36 publications
3
51
1
1
Order By: Relevance
“…This finding is similar to those of other reports of haemodynamic changes during both low and high frequency TENS. 10,20 There are no other published investigations on the effect of continuous TENS treatment and ambulatory blood pressure monitoring and the present study indicates that Lo-TENS may reduce blood pressure. There are, however, some important limitations to the study design that must be taken into account, such as a small number of subjects which makes the statistics vulnerable.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…This finding is similar to those of other reports of haemodynamic changes during both low and high frequency TENS. 10,20 There are no other published investigations on the effect of continuous TENS treatment and ambulatory blood pressure monitoring and the present study indicates that Lo-TENS may reduce blood pressure. There are, however, some important limitations to the study design that must be taken into account, such as a small number of subjects which makes the statistics vulnerable.…”
Section: Discussionmentioning
confidence: 47%
“…19 The proposed mechanisms behind the anti-ischaemic effect in coronary artery disease are contradictory. 20,21 Chauhan et al have demonstrated that TENS increased coronary blood flow at rest in patients with coronary artery disease and syndrome-X, 20 whereas other studies on TENS and spinal cord stimulation have shown a decrease in myocardial oxygen consumption. 21 The heart rate was unaffected throughout the study.…”
Section: Discussionmentioning
confidence: 99%
“…In 1994, Chauhan et al showed an increase in coronary flow velocity in patients with refractory angina, during only 5 minutes' TENS. 117 In contrast to their findings, observations in an anesthetized canine preparation of SCS, in which myocardial ischemia was created through a 4 minute ligation of a coronary artery, followed by application of radiolabeled microspheres to evaluate myocardial ischemia, suggest that blood flow in the microcirculation was not affected. 118 Albeit that the occlusion was of very short duration and the canines did not show atherosclerotic coronary artery disease, this finding should not be surprising since it has been shown that the sympathetic nervous system does not seem to influence native coronary collateral vessels in canine myocardium.…”
Section: Electrical Neuromodulation and Myocardial Ischemiamentioning
confidence: 78%
“…In this context, TENS is presented as a potential therapeutic resource able to interact in different clinical conditions, such as hypertension, in addition to its analgesic effects widely described in literature (Chesterton et al, 2002;Sbruzzi et al, 2012;Vance et al, 2014;Bi et al, 2015). This interaction of TENS with the cardiovascular system is demonstrated by vasodilation (Cramp et al, 2000;Miller, Gruben, & Morgan, 2000;Sherry et al, 2001;Vieira et al, 2012), increased blood in peripheral and coronary blood flow (Chauhan et al, 1994;Jessurun et al, 1998;Cramp et al, 2000;Miller et al, 2000;Sandberg, Sandberg, & Dahl, 2007), decreased peripheral vascular resistance (Mannheimer, Emanuelsson, & Waagstein, 1990;Sherry et al, 2001), and heart rate (Nitz, 2003). The combination of these mechanisms reduces the blood pressure demonstrated in healthy volunteers (Sherry et al, 2001;Nitz, 2003;Vieira et al, 2012) and in hypertensive patients (Kaada et al, 1991;Jacobsson et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic techniques that correct this imbalance are associated with reduced cardiovascular mortality (European Society of Cardiology [ESC], 1996). TENS is presented as a potential non-pharmacological resource that can be applied in the management of some cardiovascular diseases, such as hypertension (Chauhan et al, 1994;Cramp, Gilsenan, Lowe, & Walsh, 2000;Raimundo et al, 2009;Stein et al, 2011). Previous studies have demonstrated that TENS application reduced the systemic blood pressure of healthy volunteers (Sherry, Oehrlein, Hegge, & Morgan, 2001;Nitz, 2003;Vieira et al, 2012) and hypertensive patients (Kaada, Flatheim, & Woie, 1991;Jacobsson, Himmelmann, Bergbrant, Svensson, & Mannheimer, 2000).…”
Section: Introductionmentioning
confidence: 99%